Distinct Differences in Repertoires of Low-Molecular-Mass Secreted Antigens of Mycobacterium avium Complex and Mycobacterium tuberculosis - Olsen, Ingrid (American Society for Microbiology, 2000)
Antigens in a 4-week-old culture filtrate (CF) of Mycobacterium avium subsp. avium were separated in sodium dodecyl sulfate-polyacrylamide gel electrophoresis and identified by Western blotting. The culture had minimal lysis of bacilli, giving a CF preparation consisting mainly of secreted proteins. Comparison with a similar CF of Mycobacterium tuberculosis with almost no contamination with intracellular proteins showed the presence of cross-reactive antigens homologous to the four components of the antigen 85 complex, as well as MPT32. These were major constituents of the M. avium subsp. avium CF. In addition, there were several low-molecular-mass bands (<15 kDa) in both species that did not cross-react with polyclonal and polyvalent rabbit antibodies in Western blotting. Furthermore, these bands were not detected in corresponding sonicate preparations, indicating high localization indexes, which is typical of soluble secreted proteins. A 14-kDa protein was selected for purification and more detailed characterization. The N-terminal amino acid sequence was determined, and a matching gene was found within the genomic sequence of M. avium subsp. avium which was highly homologous to Rv0455c of M. tuberculosis. The gene encoded a signal peptide typical of secreted mycobacterial proteins. A rabbit antiserum was raised against the purified protein, and the antigen was demonstrated by Western blotting in CFs of M. avium subsp. avium, Mycobacterium avium subsp. paratuberculosis, Mycobacterium intracellulare, and Mycobacterium scrofulaceum but was not detected in M. tuberculosis. This is a new example of a highly homologous gene being differentially expressed by different mycobacterial species.